THE WONDERLAND DANCE PERFORMANCE AS A CULTURAL EXCHANGE ACTIVITY IN KAMPUNG TANJUNG SURAT, JOHOR, MALAYSIA - Hesti Desba Yesa; Fany Puspita Sari Tampubolon; Sri Oktaviani Nababan; Irfan Syahputra; Jefri Saputra; Nadya Febriani Mokerze; Rasyid Ridho Harahap; Dahrul Aman Harahap Ramses; Suryo Hartanto; Hanafi Siregar; Asmaul Husna; Muhammad Azali Bin Muhammadon (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This article discusses the implementation of the Wonderland Dance performance as part of a community service program. The background of this activity is the urgency to preserve and introduce Indonesian culture in the midst of globalization, where traditional values often face challenges from modern culture. The objective was to promote Indonesian cultural identity while providing students with learning opportunities in leadership, teamwork, and cultural diplomacy. The method included several stages, namely choreography preparation, costume arrangement, coordination with local authorities in Kampung Tanjung Surat, Johor, Malaysia, and the final performance. Data were obtained through observation and informal interviews, then analyzed descriptively. The results showed that the Wonderland Dance was enthusiastically welcomed by the local community, with active participation and appreciation. Students also gained valuable experience in cultural exchange and organizational skills. In conclusion, cultural performances such as the Wonderland Dance can serve as effective media for cultural introduction, strengthening social relations, and empowering communities. Furthermore, this activity illustrates how higher education institutions can contribute to cultural preservation through community engagement. It highlights the significance of student involvement in promoting local wisdom, ensuring that Indonesian traditions continue to be recognized and appreciated in a global context.